THE SPECIFICITY OF ALLERGIC REACTIONS : VI. UNRESPONSIVENESS TO SIMPLE CHEMICALS - Coe, John E. (The Rockefeller University Press, 1963)
"Gastric feeding" of adult guinea pigs with dinitrochlorobenzene (DCB) resulted in a specific unresponsiveness to sensitization with the specific contact hapten. The more DCB gastric-fed to a guinea pig, the more complete the unresponsiveness to the hapten. When mycobacteria were incorporated into the sensitizing emulsion, the state of unresponsiveness to the dinitrophenyl (DNP) group was less apparent. When animals gastric-fed with DCB were later sensitized with an in vitro conjugate of the hapten combined with a heterologous protein such as dinitrophenyl-hen egg albumin (DNP·HEA), an immune response similar to that in the controls occurred both to the hapten and to the protein carrier. However, when the tolerant animals were sensitized with a conjugate containing a homologous protein carrier such as dinitrophenyl guinea pig serum (DNP·GPS), they showed diminished immune responses in comparison with those in the non-tolerant controls. The presence of circulating anti-DNP antibodies from sensitization with DNP-HEA did not affect the unresponsiveness to the specific contact hapten, regardless of whether these antibodies are present before or after induction of tolerance. Sensitization with picryl chloride (PiCl) (a cross-reacting hapten), either before or after gastric feeding of DCB, did not affect the state of unresponsiveness to DNP. Similarly when the DNP-tolerant animal was sensitized with PiCl, the subsequent immune response was similar to that in the controls; cross-reactions with the DNP group both in the contact and circulating antibody phase occurred at a rate similar to that in the controls. The foregoing relationships can be explained by presuming that, upon the gastric feeding of DCB, an in vivo conjugate is formed with a somatic protein, which determines the basic specificity of the tolerance. Acquired tolerance seems to manifest an immunologic specificity similar to that of delayed hypersensitivity, a relationship not unexpected if delayed hypersensitivity is an early phase of the immune response.